Phosphorus immobilization in micropores of drinking-water treatment residuals: implications for long-term stability - Harris, Willie G.; O'Connor, George A.; Obreza, Thomas A.; Makris, Konstantinos C. (My University, 2004)
Drinking-water treatment residuals (WTRs) can immobilize excess soil phosphorus (P), but little is known about the long-term P retention by WTRs. To evaluate the long-term P sorption characteristics of one Fe- and one Al-based WTR, physicochemical properties pertinent to time-dependency and hysteresis of P sorption were assessed. This study also investigated the P sorption mechanisms that could affect the long-term stability of sorbed P by WTRs. Phosphorus sorption kinetics by the WTRs exhibited a slow phase that followed an initial rapid phase, as typically occurs with metal hydroxides. Phosphorus sorption maxima for both Fe- and Al-based WTRs exceeded 9100 mg of P kg-1 and required a greater specific surface area (SSA) than would be available based on BET-N2 calculations. Electron microprobe analyses of cross-sectional, P-treated particles showed three-dimensional P sorption by WTRs. Carbon dioxide gas sorption was greater than N2, suggesting steric restriction of N2 diffusion by narrow micropore openings. Phosphorus-treated CO 2 SSAs were reduced by P treatment, suggesting P sorption by micropores (5-20 Å). Mercury intrusion porosimetry indicated negligible macroporosity (pores > 500 Å). Slow P sorption kinetics by WTRs may be explained by intraparticle P diffusion in micropores. Micropore-bound P should be stable and immobilized over long periods.
Keywords: Carbon dioxide; Porosimeters; Sorption; Water treatment; Drinking-water treatment residuals (WTR); Phosphorus immobilization